2020
DOI: 10.13106/jafeb.2020.vol7.no6.277
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Assessment of Organizational Commitment and Job Performance: Vietnam Small and Medium-Sized Enterprises

Abstract: Research on employee commitment to the organization is necessary for human resource management, and the result is applied in practice to improve organizational effectiveness. The aim of the present study is to explore factors affecting organizational commitment at the small and medium-sized enterprises (SMEs) in Vietnam. Besides, the relationship between organizational commitment and job performance is examined as well. The research was conducted on a sample consisting of 67 white-collar workers and 260 blue-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
(13 reference statements)
0
9
0
1
Order By: Relevance
“…It is measured by the outer loading coefficient and Average Variance Extracted (AVE). All the outer loadings coefficients of the observed variables in Figure 2 were greater than 0.5, which meant that the observed variables explained at least 50% of the parent latent variable (Vuong et al, 2020b). Besides, the AVE coefficient of all scales was higher than 0.5, meeting the evaluation criteria of Giao et al (2020b).…”
Section: Results and Conclusionmentioning
confidence: 91%
“…It is measured by the outer loading coefficient and Average Variance Extracted (AVE). All the outer loadings coefficients of the observed variables in Figure 2 were greater than 0.5, which meant that the observed variables explained at least 50% of the parent latent variable (Vuong et al, 2020b). Besides, the AVE coefficient of all scales was higher than 0.5, meeting the evaluation criteria of Giao et al (2020b).…”
Section: Results and Conclusionmentioning
confidence: 91%
“…Kebanyakan mereka rapuh karena hanya bermodalkan pertemanan dengan pejabat/ Pengusaha. Dengan mempertimbangkan kondisi tersebut, maka pemberdayaan UMKM menjadi suatu yang niscaya dan perlu dilakukan karena melalui penguatan UMKM di yakini akan dapat di capai pemulihan ekonomi (Ceric, 2017;Švárová & Vrchota, 2014;Vuong et al, 2020).…”
Section: Pendahuluanunclassified
“…In such circumstances, employees easily accept the organizational culture of the company. Vuong et al (2020) showed that dimensions of transformational leadership and employees' trust in managers have a significantly positive influence on organizational commitment. In addition, Jatmiko et al, (2020) also reveals that contingent reward has a significant correlation with affective and normative commitment.…”
Section: Organizational Commitmentmentioning
confidence: 99%